Healthcare Professionals' Attitudes Toward Patients With Mental Illness: A Cross-Sectional Study in Qatar - Ghuloum, Suhaila; Mahfoud, Ziyad R.; Al-Amin, Hassen; Marji, Tamara; Kehyayan, Vahe (Frontiers in Psychiatry, 2022)
Background: Negative attitudes towards mental illness by Health Care Professionals (HCP) have been reported in many countries across the world. Stigmatizing attitudes by HCP can have adverse consequences on people with mental illness from delays in seeking help to decreased quality of care provided. Assessing such attitudes is an essential step in understanding such stigma and, if needed, developing and testing appropriate and culturally adapted interventions to reduce it. Aims: to assess physicians and nurses attitudes towards mental illness and to determine associated factors with different levels of stigma. Methods: A cross-sectional survey was conducted among Physicians and Nurses. The Mental Illness Clinician’s Attitudes (MICA) scale was used to assess attitudes toward mental illness. MICA scores range between 1 and 6 with higher values indicating higher stigmatizing attitudes. Demographic and work related information were also gathered. Descriptive statistics along with multivariate linear and multivariate logistic regression models were used. Results: A total of 406 nurses and 92 doctors participated in the study. The nurses’ mean MICA score was significantly higher than that of the physicians. Among nurses, being Asian and working in a geriatric, rehabilitation and long-term care facility were associated with lower MICA scores. Among physicians, being female or graduating more than one year ago were also associated with lower MICA scores. Conclusion: Stigmatizing attitudes towards people with mental illness by healthcare workers are present in Qatar. They are higher among nurses as compared to physicians. Factors associated with higher stigmatizing attitudes could be used in creating appropriate intervention to reduce the magnitude of the problem.